American Jewish thought since 1934 : writings on identity, engagement, and belief - Marmur, Michael; Ellenson, David Harry, 1947- (Tauber Institute for the Study of European Jewry series (Unnumbered), 2020)
"War and Enlightenment in Russia explores how members of the military during the reign of Catherine II reconciled Enlightenment ideas about the equality and moral worth of all humans with the Russian reality based on serfdom, a world governed by autocracy, absolute respect for authority, and subordination to seniority. While there is a sizable literature about the impact of the Enlightenment on government, economy, manners, and literature in Russia, no analytical framework that outlines its impact on the military exists. Eugene Miakinkov's research addresses this gap and challenges the assumption that the military was an unadaptable and vertical institution. Using archival sources, military manuals, essays, memoirs, and letters, the author demonstrates how the Russian militaires philosophes operationalized the Enlightenment by turning thought into reality."--